2022
DOI: 10.1371/journal.pone.0262769
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic inhibition of lumbosacral sensory neurons alleviates visceral hypersensitivity in a mouse model of chronic pelvic pain

Abstract: The study investigated the cellular and molecular mechanisms in the peripheral nervous system (PNS) underlying the symptoms of urologic chronic pelvic pain syndrome (UCPPS) in mice. This work also aimed to test the feasibility of reversing peripheral sensitization in vivo in alleviating UCPPS symptoms. Intravesical instillation of vascular endothelial growth factor A (VEGFA) was used to induce UCPPS-like symptoms in mice. Spontaneous voiding spot assays and manual Von Frey tests were used to evaluate the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The PI3K /Akt pathway has been reported as a regulator of spinal plasticity in the rat visceral pain model ( 56 ) and associated with chronic pain ( 57 ). Previous studies described an increased production of VEGF by intestinal mucosa cells of patients with IBS and associated vascular endothelial growth factors with visceral hyperalgesia, abdominal discomfort, and/or pelvic pain ( 58 , 59 ). Likewise, the neurotrophin pathway promotes blood vessel growth ( 60 ); neurotrophins such as NT-3 control the sympathetic innervation of blood vessels ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 97%
“…The PI3K /Akt pathway has been reported as a regulator of spinal plasticity in the rat visceral pain model ( 56 ) and associated with chronic pain ( 57 ). Previous studies described an increased production of VEGF by intestinal mucosa cells of patients with IBS and associated vascular endothelial growth factors with visceral hyperalgesia, abdominal discomfort, and/or pelvic pain ( 58 , 59 ). Likewise, the neurotrophin pathway promotes blood vessel growth ( 60 ); neurotrophins such as NT-3 control the sympathetic innervation of blood vessels ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 97%
“…Despite these clinical findings, the sites, and mechanisms of VEGF action in the CNS centers controlling micturition and pelvic pain, and the effects on the excitability of peripheral and central neurons innervating the LUT are poorly understood. Preclinical animal models determined that activation of VEGF signaling in the urinary bladder enhanced innervation of the bladder wall (Cheppudira et al, 2008;de Rijk et al, 2022;Malykhina et al, 2012) and that intravesical instillations of VEGF in mice promoted sensory and motor nerve density, triggered detrusor overactivity, and worsened pelvic sensitivity (Malykhina et al, 2012;Xie et al, 2022). In animal studies, silencing of lumbosacral sensory neurons with intrathecal delivery of DREADDs (designer receptors exclusively activated by designer drugs) reversed VEGF-induced visceral hypersensitivity (Xie et al, 2022), and the use of anti-VEGF antibodies effectively reduced pelvic nociception, suggesting potential benefits of anti-VEGF therapy in UCPPS patients (Lai et al, 2017).…”
Section: Transcranial Magnetic Stimulation (Tms) Is a Non-invasive Fo...mentioning
confidence: 99%
“…Preclinical animal models determined that activation of VEGF signaling in the urinary bladder enhanced innervation of the bladder wall (Cheppudira et al, 2008;de Rijk et al, 2022;Malykhina et al, 2012) and that intravesical instillations of VEGF in mice promoted sensory and motor nerve density, triggered detrusor overactivity, and worsened pelvic sensitivity (Malykhina et al, 2012;Xie et al, 2022). In animal studies, silencing of lumbosacral sensory neurons with intrathecal delivery of DREADDs (designer receptors exclusively activated by designer drugs) reversed VEGF-induced visceral hypersensitivity (Xie et al, 2022), and the use of anti-VEGF antibodies effectively reduced pelvic nociception, suggesting potential benefits of anti-VEGF therapy in UCPPS patients (Lai et al, 2017). A transcriptome study of bladder biopsy samples from IC/BPS patients with Hunner's lesions found overexpression of VEGF and B-cell activating factor in the urinary bladder.…”
Section: Transcranial Magnetic Stimulation (Tms) Is a Non-invasive Fo...mentioning
confidence: 99%
“…In lower urinary tracts, the TRPA1 channel has been implicated in overactive bladder, 11 or bladder pain 12–14 through afferent nerves 8–12 . The TRPA1 channel expression level is increased in the urinary bladders or the dorsal root ganglion (DRG) L6‐S1 in diseases such as spinal cord injury 15 or bladder and prostate inflammation 16–18 . Furthermore, it is reported that TRPA1 channels expressed within capsaicin‐sensitive afferent nerve fibers in the rat bladders mediate the basal tone of bladder strip activity 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] The TRPA1 channel expression level is increased in the urinary bladders or the dorsal root ganglion (DRG) L6-S1 in diseases such as spinal cord injury 15 or bladder and prostate inflammation. [16][17][18] Furthermore, it is reported that TRPA1 channels expressed within capsaicin-sensitive afferent nerve fibers in the rat bladders mediate the basal tone of bladder strip activity. 19 This study determined that the TRPA1 channels located in the urinary bladder could mediate the LT-elicited bladder overactivity in normal rats.…”
Section: Introductionmentioning
confidence: 99%